2022
DOI: 10.1021/acs.energyfuels.2c01109
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Depolymerization of a Kraft Lignin by a Mechanochemical Approach

Abstract: Kraft lignin is an abundantly available side product from the pulp and paper industry. It has a complex aromatic structure and has great potential to serve as a feedstock for renewable aromatic chemicals. In this communication, we show that a simple mechanochemical pretreatment (viz., ball milling) of commercial Indulin AT kraft lignin before solvent-free hydrotreatment results in a 15% increase in the recovered oil yield with 15% more alkylphenols and a 33% reduction in solids compared to the unmilled sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…During heating, the lignin will melt at around 150 °C and then, together with products thereof, act as the solvent. 34 After 4 h, the reactor was cooled to room temperature at an approximate rate of 10 °C/min. The pressure and temperature at room temperature were recorded for calculation of the H 2 consumption and quantification of the gaseous products.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…During heating, the lignin will melt at around 150 °C and then, together with products thereof, act as the solvent. 34 After 4 h, the reactor was cooled to room temperature at an approximate rate of 10 °C/min. The pressure and temperature at room temperature were recorded for calculation of the H 2 consumption and quantification of the gaseous products.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The reactor was heated to 400 °C with a heating rate of about 8 °C/min, and the time was set at zero when the predetermined temperature was reached. During heating, the lignin will melt at around 150 °C and then, together with products thereof, act as the solvent . After 4 h, the reactor was cooled to room temperature at an approximate rate of 10 °C/min.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Hydrogenolysis specifically targets the cleavage of carbon–carbon or carbon–heteroatom bonds, followed by stabilization via the addition of an H atom. Homogenous catalysts can effectively cleave ether bonds in lignin, but difficult separations and low product purity are common disadvantages . Alternatively, solid catalysts, such as supported Ni, Pd, or Pt, allow for easier separation under reasonably mild conditions, but contacting them with a solid feedstock like lignin that is insoluble in most common solvents is a significant challenge. ,, Pd was specifically chosen as the primary active metal for this study due to its ability to form interstitial hydrides as a hydrogen storage reservoir, which is advantageous in facilitating hydrogenolysis reactions. …”
mentioning
confidence: 99%
“…Several studies of mechanocatalysis as an approach to depolymerizing lignocellulosic biomass and lignin model compounds have been conducted. ,, Rinaldi et al demonstrated the depolymerization of both cellulose and biomass to water-soluble sugars and furfurals with complete conversion and yields of water-soluble oligosaccharides and lignin oligomers exceeding 90%. Bolm’s works have examined the conversion of lignin model compounds representing β-O-4 linkages in base-catalyzed and oxidative reactions . The base-catalyzed reactions produced monomer yields of up to 94%, while the oxidative transformation resulted in aryl-c α cleavage of the β-O-4 model, resulting in quinone (91% yield) and guaiacol (82% yield) as the two main products.…”
mentioning
confidence: 99%